Studies on Schismatoglottideae (Araceae) of Borneo VIII : A Review of Piptospatha elongata in Sarawak. - Wong Sin, Yeng; P. C., Boyce; J., Bogner (Singapore Botanic Garden, 2009)
A review of Piptospatha elongata (Engl.) N. E. Br. in Sarawak is present. The species is shown to comprise three morphologically and ecologically distinct taxa, two of which are new to science and herewith described as Piptospatha impolita S. Y. Wong, P. C. Boyce & Bogner and P. viridistigma S. Y. Wong, P. C. Boyce & Bogner. A new key to Piptospatha is presented and all species of the Elongata group are illustrated. Additionally, new observations on the morphologies separating the Piptospatha elongata Group and P. graboskii Group sensu Bogner and Hay (2000) are presented.